Live birth rates in In vitro fertilization cycles with oocytes containing smooth endoplasmic reticulum aggregates and normal oocytes - Sumana Gurunath; Reeta Biliangady; Uma Maheshwari Sundhararaj; Ambika Gangadharswamy; Swathi Gundlapalli; G Murali Mohan Reddy (Wolters Kluwer Medknow Publications, 2019)
Aims: The aims of this study were to compare the live birth, embryological and pregnancy outcomes after intracytoplasmic sperm injection (ICSI) in patients who have oocytes with smooth endoplasmic reticulum aggregates (SERa+ cycles) and patients with normal oocytes and to compare the pregnancy outcomes based on the observed frequency of SERa. Settings and Design: The current study was a retrospective case record review of patients undergoing ICSI from 2012 to 2016 in a specialty fertility center. Materials and Methods: The patients were divided into two groups based on the presence of SERa: patients with at least one oocyte containing SERa (SERa+ cycles) (n = 112) and patients with normal oocytes (n = 839). The primary outcome measure was live birth rate. The secondary outcome measures were fertilization rate, cleavage rate, blastocyst formation rate, clinical pregnancy rate, miscarriage rate, and anomalies in children born. Results: Women with SERa+ cycles showed similar live birth rates, fertilization rates, cleavage rates, blastocyst formation rates, clinical pregnancy rates, miscarriage rates, and abnormalities in children compared to women with normal oocytes. A gradual reduction in live birth rates was observed when the percentage of oocytes containing SERa increased. The group containing >50% of oocytes with SERa demonstrated no live births. Conclusions: Presence of SERa had no major overall negative impact on key embryological and live birth outcomes. A reduction in the live birth rate with increasing proportion of SERa oocytes was observed, with no live births in the group with >50% or all affected oocytes.